2015
DOI: 10.1017/s1751731115001639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex, dietary glycerol or dietary fat during late fattening, on fatty acid composition and positional distribution of fatty acids within the triglyceride in pigs

Abstract: The effect of sex, source of saturated fat (lard v. palm oil) and glycerol inclusion in the fattening diet on composition and fatty acid positional distribution in the triglyceride molecule was studied in pigs from 78 to 110 kg BW. Average daily gain and carcass characteristics, including ham and loin weight, were not affected by dietary treatment but sex affected backfat depth ( P < 0.01). A significant interaction between sex and glycerol inclusion was observed; dietary glycerol increased lean content in gil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…A sex-related effect on the FA profile has been reported in many studies (Segura et al 2015a;Daza et al 2016;Egea et al 2016). Differences between males and females were similar in SCF, IMF and the PL fraction of the liver.…”
Section: Effect Of Offspring Birthweight and Sex On Carcass And Meat supporting
confidence: 57%
“…A sex-related effect on the FA profile has been reported in many studies (Segura et al 2015a;Daza et al 2016;Egea et al 2016). Differences between males and females were similar in SCF, IMF and the PL fraction of the liver.…”
Section: Effect Of Offspring Birthweight and Sex On Carcass And Meat supporting
confidence: 57%
“…This finding supports the theory that there is a limited possibility of altering FA composition at the sn-2 location of the TAG by dietary intervention during the fattening phase (Segura et al 2015a). This is a matter of interest, because it is believed that SFA in the sn-2 position have a more detrimental health effect than those located in the external sn-1,3 location (Berry 2009), thus negatively affecting pork consumer acceptability.…”
Section: Resultssupporting
confidence: 87%
“…Innis et al (1997) provided diets differing in total FA composition and distribution within the TAG, they studied the liver lipids of piglets and reported a limited effect of dietary treatment, and therefore suggested metabolic regulation of FA composition in sn-2 position. Segura et al (2015a) also found a limited effect of either sex or dietary treatment on the FAs located in the internal sn-2 position of pig SF. Gastric and pancreatic lipases hydrolyze FA from the external positions of the TAG.…”
Section: Resultsmentioning
confidence: 84%
“…5 EXT: IB × DR pigs free-range reared and exclusively fed on acorns and grass according to the traditional feeding system. 6 SFA (saturated fatty acids) = C14:0 + C15:0 + C16:0 + C17:0 + C18:0 + C20:0, 7 MUFA (monounsaturated fatty acids) = C16:1n-7 + C17:1 + C18:1n-9 + C10:1n-9, 8 PUFA (polyunsaturated fatty acids) = C18:2n-6 + C18:3n-3 + C20:3n-6 + C20:4n-6, 9 UI (unsaturation index) = [(C16:1n-7 + C17:1 + C19:1n-9 + C20:1n-9) + 2 × C18:2n-6 + 3 × (C18:3n-3 + C20:3n-6) + 4 × C20:4n-6], 10 Σn-6/Σn-3 = (C18:2n-6 + C20:3n-6 + C20:4n-6)/C18:3n-3.…”
Section: Resultsmentioning
confidence: 99%
“…Studies aimed to control the FA distribution by dietary intervention in pigs are scarce and evidence that the FA composition in the internal sn-2 position is highly regulated and resistant to dietary manipulation [7,9], thus maintaining a narrow range of variation. Accordingly, previous studies in pigs evaluated the effects, such as dietary glycerol or saturated diets, that resulted in limited modifications at the sn-2 position in the TAG [10]. Other dietary supplementations, such as the use of compounds that reduce the ∆ 9 -desaturase enzyme activity, have been related to an increase in the proportion of saturated FA at the sn-1,3 position [9].…”
Section: Introductionmentioning
confidence: 99%